Efektivitas Fotodegradasi Lignin dari Limbah Ampas Sagu (Metroxylon sagu Rottb.) Menggunakan Katalis TiO₂: The Effectiveness of the Photodegradation of Lignin from Sago (Metroxylon sagu Rottb.) Waste Using TiO₂ Catalyst - Muh. Natsir; Aden Mula Pratiwi; Thamrin Azis; Nohong; Imran; Wa Ode Harlis; Alimin; La Ode Kadidae; Ruslan; C Bijang; La Ode Abd Kadir; Laily Nurliana (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Lignin degradation from sago (Metroxylon sagu Rottb.) waste has been carried out using a TiO2 catalyst. This research aims to determine the effectiveness of lignin degradation from sago waste using a TiO2 catalyst. Lignin from sago pulp was isolated using 10% NaOH and characterized using Fourier Transform Infra Red (FTIR) spectroscopy. The results of the characterization using FTIR show that the absorption at wave number 2937.59 cm-1 is the -C-H stretching vibration of the alkane functional groups, the absorption at wave number 2360.87 cm-1 is the vibration of the C≡C triple bond, the wave numbers 1795.73 cm-1 and 1637.56 cm-1 are associated with the stretching of the carbonyl group. The absorption at wave number 1427.32 cm-1 is a C-H vibration connected to an unsaturated bond in an aromatic ring. Absorptions at wave number 1105.21 cm-1, 1128.36 cm-1, 1153.43 cm-1 were the stretching vibration of -C-H on the guaiasil ring, and the absorption at wave number 1022.27 cm-1 was the stretching vibration of C-O-C ether. From this spectrum, it can be seen that lignin is not completely pure because it is probably still mixed with cellulose. The results of the effectiveness test of lignin degradation using a TiO2 catalyst with the help of UV light were able to degrade the lignin isolated by 31.43%, for 3 hours at a lignin concentration of 40 ppm.